Effect of Oral Supplementation for Rabbits of Pomegranate seed Extract on Some Serum Biochemical Parameters in Relation to oral Inflammation, oxidative stress, and wound healing - Rezan M Omer; Dilyar A Baban; Bakhtiar M Ahmed (College of Dentistry/ University of Baghdad, 2019)
Background: Pomegranate (punicagranatum L, Punicaceae), is an edible fruit consumed around the world. The edible part of pomegranate is rich in compounds that possess antioxidant and anti-inflammatory activities. The aim of this study is to investigate the antioxidant; anti-inflammatory and gingival wound healing effects of Punicagrantum L. seed extract oral supplementation in rabbit. Methods and Methods: Forty five male rabbits were divided into 3 groups, base line (5 rabbits) left without buccal gingival wound as( group 1),study group, 20 rabbits (group2) with buccal gingival wound treated with ethanolic extract of Punicagranatum L. seed extract and control, 20 rabbits (group 3) with buccal gingival wound only. Buccal gingival wounds were created on lower right central incisor and sutured removed after (7) days. Blood biopsies by cardiocentesis were collected at times (0, 3h, 1, 3 and 7days) for estimation of serum alkaline phosphatase activity, serum total proteins, and serum uric acid. Results: The results showed a significant increase in serum Alkaline phosphatase, total proteins and uric acid in all time intervals after buccal gingival wound, in rabbits receiving water, while their levels increased significantly only at time intervals of 3 hours and 1 day after gingival wound, in rabbits receiving pomegranate seed extraction. Conclusions: It has been concluded that oral Supplementation of pomegranate seed extract in rabbits can expedite the rate of healing of gingival wound